Variability of the Aerosol Content in the Tropical Lower Stratosphere from 2013 to 2019: Evidence of Volcanic Eruption Impacts - Tidiga, Mariam (2022)
This paper quantifies the tropical stratospheric aerosol content as impacted by volcanic events over the 2013–2019 period. We use global model simulations by the Whole Atmosphere Community Climate Model (WACCM) which is part of the Community Earth System Model version 1.0 (CESM1). WACCM is associated with the Community Aerosol and Radiation Model for Atmospheres (CARMA) sectional aerosol microphysics model which includes full sulphur chemical and microphysical cycles with no a priori assumption on particle size. Five main volcanic events (Kelud, Calbuco, Ambae, Raikoke and Ulawun) have been reported and are shown to have significantly influenced the stratospheric aerosol layer in the tropics, either through direct injection in this region or through transport from extra-tropical latitudes. Space-borne data as well as ground-based lidar and balloon-borne in situ observations are used to evaluate the model calculations in terms of aerosol content, vertical distribution, optical and microphysical properties, transport and residence time of the various volcanic plumes. Overall, zonal mean model results reproduce the occurrence and vertical extents of the plumes derived from satellite observations but shows some discrepancies for absolute values of extinction and of stratospheric aerosol optical depth (SAOD). Features of meridional transport of the plumes emitted from extra-tropical latitudes are captured by the model but simulated absolute values of SAOD differ from 6 to 200% among the various eruptions. Simulations tend to agree well with observed in situ vertical profiles for the Kelud and Calbuco plumes but this is likely to depend on the period for which comparison is done. Some explanations for the model– measurement discrepancies are discussed such as the inaccurate knowledge of the injection parameters and the presence of ash not accounted in the simulations.